Uncommon onset of lower urinary tract symptoms in a young adult: The impact of a large utricle cyst in a young adult - El Abidi Hamza; Ziani Idriss; Tariqi Reda; Mikou Mohamed Ali; Ibrahimi Ahmed; Boualaoui Imad; El Sayegh Hashem; Nouini Yassine (Urology Case Reports)
Lower urinary tract symptoms (LUTS) in young adults are uncommon, making diagnosis difficult. This report describes the case of a young adult with no medical history who developed LUTS, which included urgency, nocturia, dysuria, and pelvic pain that lasted six months. The absence of fever or infectious symptoms raised concerns about atypical etiologies. Comprehensive testing, including bacterial urine and sperm screening, ruled out an infectious cause. Imaging indicated that the underlying cause was a prostatic utricle cyst, which is an embryological remnant that goes unnoticed in many cases but may cause symptoms when it is large. The successful endoscopic excision of the cyst resulted in total discomfort relief.